Great civilizations. (Parragon, 2011)
From the familiar tales from Greece and Rome and the opulence of the major Chinese dynasties, to the great empires of Egypt and Mesopotamia, Great Civilizations encompasses the rise and fall, victories an defeats, leaders and subjects, of many diverse and magnificent cultures.